High Prevalence of Dyslipidemia in Type 2 Diabetics: Strong Association with Obesity, Poor Glycemic Control, and Smoking - Beena Zehra, Urva Khan, Bushra Hussain, Saleha Afridi, Aqsa Sabuhi, Nasir Jamil (Pakistan Journal of Medical & Health Sciences, 2023)
In the current research article, the researcher examined and studied the prevalence of and risk factors of dyslipidemia among patients with T2DM at a tertiary care hospital in Lahore, Pakistan, its correlation with obesity, poor glycemic control, and smoking. Dyslipidemia is a widespread and fatal metabolism disorder in T2DM that greatly increases the risk of cardiovascular disease. Even though diabetes is a significant problem in Pakistan, little is known about the extent and distribution of dyslipidemia and its preventable risk factors. A cross-sectional analysis was done on 250 T2DM patients between January and August 2023. Patients taking lipid-lowering medications or who had secondary dyslipidemia were excluded. Lipid profiles, glycated hemoglobin (HbA1c), and BMI, as well as smoking status were checked. Dyslipidemia was determined according to the ADA. The prevalence of dyslipidemia was 96.4%. An increase in the triglyceride content was the most frequently reported disruption (82.8%), followed by LDL-C (76.8%) and low HDL-C (72.4%). Mixed dyslipidemia pattern occurred in 71.6 percent of the subjects. Dyslipidemia was strongly linked with obesity (p < 0.001) where 98.2 percent of individuals with obesity had it. Equally poor glycemic control (HbA1c flanking 7%) was pronouncedly associated with dyslipidemia (98.4%, p < 0.001) and 100 pct of the current smokers suffered dyslipidemia in the test. Obesity, uncontrolled HbA1c and smoking were independent predictors confirmed by logistic regression. This research points to a very high rate of dyslipidemia in Pakistani patients with T2DM and advises the introduction of early screening measures and combined obesity treatment, glycemic measures, and smoking cessation interventions to decrease the risk of cardiovascular diseases. Keywords: Dyslipidemia, Type 2 Diabetes, Obesity, Glycemic Control, Smoking